On modelling of the one dimensional pseudoelastic effect of shape memory alloys - Zidane Imade; Meddour Belkacem (Mechanics & Industry)
Last decades, a qualitative leap in materials engineering was observed, through developing new materials or discovering new properties. The shape memory alloys are a group of materials exhibiting singular behaviour under a coupled thermomechanical loading, and they are widely used in numerous applications because of their properties. To exploit these properties in engineering, several constitutive models of were developed. The aim of this work is to build a constitutive model that could describe the pseudoelastic behaviour of shape memory alloys in a simpler and more accurate way. Based on thermodynamics and mechanics laws and principles, the developed constitutive model was implemented in an algorithm and compared with experimental data in order to assess its accuracy. The obtained results indicated that the agreement between the real and computer-simulated stress-strain curves was good. This reaffirmed the model's ability to predict the pseudoelastic behaviour of the shape memory materials under various loading states. These results thus validate especially the temperature sensitivity of Nitinol alloys, which should be taken into account when designing devices that need to function reliably.